Number the stars - Lowry, Lois (New York : Bantam Doubleday Dell Books for Young Readers, 1989)
In 1943, during the German occupation of Denmark, ten-year-old Annemarie learns how to be brave and courageous when she helps shelter her Jewish friend from the Nazis.
Keywords: World War, 1939-1945 -- Denmark -- Juvenile fiction; Historical fiction